Enhancing Individual Positive Reaction to Organizational Change Through Transformational Leadership and Change Agent’s Credibility - Deviana, Riszty Budi; Hendarsjah, Hidajat (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: This study aims to analyze the effect of transformational leadership and the credibility of change agents on the positive reactions of individuals. Reactions are not dichotomized into forms of support and resistance but are analyzed using a three-dimensional attitude approach: cognitive, emotional, and intentional.Design/Methodology/Approach: The population of this research was civil servants at BPS-Statistics in Central Java Province, consisting of 35 regencies/municipalities. Simple random sampling was used to sample the population; there were 304 respondents. The data were then collected by self-enumeration with an online questionnaire and analyzed with Structural Equation Modeling—Partial Least Squares (SEM-PLS).Research findings: Based on statistical results, the six hypotheses proposed demonstrated a significant positive effect on all relationships between variables. Transformational leadership and change agents' credibility positively correlated with the individual positive reactions, i.e., cognitive, emotional, and intentional reactions. Theoretical Contribution/Originality: In the theory of force fields, Kurt Lewin states that the success of organizational change can be achieved by increasing the forces that drive change. This strength can be sourced from the positive reactions of individuals in the organization, where these reactions are along the cognitive, emotional, and intentional dimensions. Understanding individual reactions through the tripartite concept provides clearer information about individual reactions to change.Practitioners/Policy Implications: By applying a transformational leadership style, positive reactions to organizational change can be comprehensively enhanced in three dimensions, i.e., cognitive, emotional, and intentional. In addition, the change agent appointed to facilitate change must also have credibility.Research Limitations/Implications: This study only analyzed the relationship between the antecedent variables and the positive reactions of individuals without considering the negative reactions. Hence, the influence of reaction ambivalence on an individual's reaction to change can also be explored in future studies.